IR-spectroscopy and AFM-microscopy of the surface of gamma-irradiated GaS and GaS:Yb layered single crystals - Pashayev, A.M.; Tagiyev, B.G.; Madatov, R.S.; Gadzhieva, N.N.; Aliev, A.A.; Asadov, F.G. (Вопросы атомной науки и техники, 2019)
For the first time, information on the surface relief of the layered GaS and doped GaS:Yb single crystals subjected to gamma-irradiation was obtained using atomic force microscopy (AFM) and Fourier-transform infrared spectroscopy (FTIR). It was found that GaS is characterized by a non-uniform distribution of irregularities with different heights and periodicities, and when doping crystals with Yb atoms, the distribution of irregularities becomes more orderly, the height and periodicity of irregularities decreases. In the FTIR spectra, changes in the reflection coefficients of the surface of GaS and GaS:Yb single crystals are observed as a function of the gammairradiation dose (Фγ = 30…200 krad), and on the basis of spectroscopic and microscopic changes, it was found that doped single crystals are the most radiation-resistant. Вперше методами атомно-силової мікроскопії (АСМ) і ІК-фур'є-спектроскопії отримано інформацію про рельєф поверхні нелегованих GaS і легованих монокристалів GaS:Yb, підданих гамма-опроміненню. Встановлено, що для монокристалів GaS характерний нерівномірний розподіл нерівностей з різною висотою і періодичністю, а при легуванні кристалів атомами Yb розподіл нерівностей упорядкується, їх висота і періодичність зменшаться. В ІК-фур’є-спектрах спостерігаються зміни коефіцієнтів відбиття поверхні монокристалів GaS і GaS:Yb в залежності від дози гамма-опромінення (Фγ = 30...200 крад), і на основі цих змін встановлено, що леговані монокристали є більш радіаційно стійкими. Впервые методами атомно-силовой микроскопии (АСМ) и ИК-фурье-спектроскопии получена информация о рельефе поверхности нелегированных GaS и легированных монокристаллов GaS:Yb, подвергнутых гамма-облучению. Установлено, что для монокристаллов GaS характерно неравномерное распределение неровностей с различной высотой и периодичностью, а при легировании кристаллов атомами Yb распределение неровностей упорядочится, их высота и периодичность уменьшатся. В ИК-фурьеспектрах наблюдаются изменения коэффициентов отражения поверхности монокристаллов GaS и GaS:Yb в зависимости от дозы гамма-облучения (Фγ = 30…200 крад), и на основе этих изменений установлено, что легированные монокристаллы являются более радиационно стойкими.